Peran Pemerintah Desa Dalam Strategi Pemberdayaan Kreativitas Camat Menggerakkan Pegawai Dalam Tugas Pemerintahan Dan Pembangunan Di Kantor Camat Taluditi - Umar Sune; Rusni Djafar (Universitas Islam Darul Ulum Lamongan, 2021)
Creativity really needs to be owned by leaders, where creativity is the ability of leaders to stimulate the thoughts or ideas of their subordinates (intellectual stimulation). Transformational leaders or intelligent leaders have ideas or analyzes that are able to enlighten their partners, in terms of leadership being able to improve the performance of their subordinates to achieve a desired organizational goal, resulting in maximum employee performance. Likewise for employees at the Taluditi Sub-district Office, Pohuwato Regency, basically potential human resources must be utilized, so that they can work optimally in the context of managing organizational goals. But in reality it can be observed, most employees have not carried out their duties and functions as public servants, are still hesitant in completing work, the tendency to find easy work, the slowness of assignments, due to the attention of the leadership (sub-district) to their subordinates. Then the camat function has not yet been implemented in terms of planning, regulation, and constructive supervision of all sub-district programs and government programs. The purpose of this study was to determine the creativity of moving employees in government and development tasks at the Taludit District Office, Pohuwato Regency. The method used in this study is qualitative as a research procedure that produces a description of the data in the form of written or spoken words from people from the observed behavior. Based on the results of the study, it can be seen that the creativity of the Taluditi Camat, Pohuwato Regency which can be realized through various ideas to mobilize employees in government and development, then these ideas are quickly responded to by the apparatus, and supported by Flexibility to determine their motivation. So that the employee can elaborate all the ideas and ideas of the Camat in realizing the goals of the Taluditi District government, Pohuwato Regency which is Healthy, Intelligent, Advanced, Prosperous and devoted to God Almighty, harmonious and religious society and realizing an advanced and competitive Region, environmentally sound, improve the quality of life of the community and good development.